High mortality and high PCDD/Fs exposure among residents downwind of municipal solid waste incinerators: A case study in China. (1st February 2022) - Ji, Guixiang; Chen, Qi; Ding, Zhen; Gu, Jie; Guo, Min; Shi, Lili; Yu, Hao; Sun, Hong
Abstract: Studies on the human body burden of dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) in populations around municipal solid waste incinerators (MSWIs) in China are limited. The objective of this study was to assess the potential adverse health effects of an 8-year MSWI on the surrounding population and identify possible exposure pathways. We hypothesized that the MSWI would result in different environmental impacts and population health outcomes between upwind and downwind of its 3 km vicinity. We conducted a 10-year retrospective mortality survey on the population surrounding the MSWI. Then, we selected 50 residents aged 50 years or older on each of the upwind and downwind sides of MSWI to test serum PCDD/Fs. Meanwhile, environmental and food exposures to PCDD/Fs were tested for selected residents. The age-adjusted mortality rates were significantly higher for residents downwind than upwind, but no significant difference was found in the standardized mortality ratio before and after the MSWI operation. The toxic equivalents (TEQ) and major congeners of PCDD/Fs were significantly higher in the sera of the downwind residents than in the upwind. The PCDD/Fs in air, soil, dust, and vegetables on the downwind side were not significantly different from those on the upwind side, but the mean concentrations of PCDD/Fs in downwind hen eggs was significantly higher than those from upwind. In conclusion, downwind residents living within 3 km of the MSWI had higher age-adjusted mortality and serum level of PCDD/Fs than upwind residents. This higher mortality rate among downwind residents was not associated with MSWI. However, the higher levels of PCDD/Fs in downwind hen eggs suggest that the downwind population dioxin exposure was related to their location. Graphical abstract: Image 1 Highlights: The mortality of residents was higher in the downwind of an 8-year operating MSWI. Serum concentrations of PCDD/Fs were significantly higher in the downwind residents. PCDD/Fs in downwind eggs exceeded the standard and were higher than upwind.